ANALISIS PROMOSI, KUALITAS PRODUK DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN MOTOR MATIC BEAT OLEH MAHASISWA UNDHARI - Rian Amdhani; Eka Erma Wati; Kelik Purwanto (MANAJEMEN DEWANTARA, 2022)
This study analyzes the effect of promotion, product quality, and brand image on purchasing decisions. The population and sample of this research are students of Dharmas Indonesia University who use beat motors as many as 100 respondents. The type of data used in this study is primary data. Methods of data collection using a questionnaire and processing using SPSS 2.6. The results showed that the promotion variable (X1) had a positive and significant effect with a significance value of 0.001 < 0.05 and a value of 3.444 > 1.985, so sig > 0.05, the independent variable had a positive and significant effect on the dependent variable. Product quality (X2) based on the results of the t-test shows that the significant value of product quality implementation on shopping interest is 0.000 <0.05 and the value is 5.992 > 1.985 indicating that there is a significant influence between product quality variables on purchasing decisions. Brand image (X3) based on the results of the t-test shows that the significant value of brand image implementation on purchasing decisions is 0.078 > 0.05 and the value of 1.780 < 1.985 indicates a positive but not significant effect between brand image variables on purchasing decisions. The results show that promotion (X1) product quality (X2) and brand image (X3) have a significant simultaneous effect on purchasing decisions (Y) with an F value with F because the F value is greater than the F value (53.730 > 2.699). F value 53,730 with a significant level (0.000 < 0.05).